English Learning Challenges: an Exploratory Mixed-Method Study for Low-Level Students - Andika Andika (Departement of Mathematics Education, 2024)
Theoretically, a communicative approach and communicative sessions based on it may seem appropriate for all teaching contexts. However, in the context of real-world classes, reality may differ, especially in mixed skill classes. This research is an attempt to raise awareness of the different types of difficulties that low-performing people face during communicative sessions in mixed-ability classes. It tries to make a connection between the principles on which the sessions are built and the difficulties that arise from mixed-skill classes. The data were collected through questionnaires and interviews for English students and teachers, as well as by observing a series of communicative sessions held as part of the ELT in Palembang. The study found that the majority of low-level students were unable to cope with the sessions. They place high demands on them, especially in connection with mixed skills. They negatively affect the self-esteem and motivation of low-performing people to learn English. The results of this study can be used to enrich and support other research dealing with similar topics. They can also help decide on adequate solutions to underperforming problems with communicative activities in the context of blended ability learning.